Efficacy of alarm intervention in primary monosymptomatic nocturnal enuresis in children - Claudius, Gourav; Chhatwal, Jugesh; Sohi, Inderpreet (International Journal of Contemporary Pediatrics, 2016)
Background: Enuresis affects about 15 to 20% of five year old children, and even up to 2% of young adults. The various treatment modalities used are behavioural therapy, alarm intervention and pharmacological therapy. Current evidences suggest that alarm intervention is preferable to other modalities of treatment. So a study was done to assess the efficacy of alarm interventions in primary monosymptomatic nocturnal enuresis in children. Methods: A prospective study was done on children aged between 5-18 years with primary monosymptomatic nocturnal enuresis on a total of 62 children. An enuresis diary was maintained by parents. All children received alarm intervention for 12 weeks. A child remaining dry for two consecutive weeks was taken as a success. The subjects were followed up for 12 weeks, two or more wet night in 2 weeks period were taken as relapse. If child failed to become dry after 12 weeks of alarm intervention, intervention was continued for maximum of 6 months or till he became dry. Results: Out of 62 children, majority were males and in the age group of 5-7 years. Family history of enuresis was present in 30.65% of children. A total of 74.19 % of subjects achieved dryness while failures were 25.8% and relapse was seen in 23.91 % during follow up. Significant improvement was noticed as early as 2 months after alarm intervention (p 0.00499) but maximum improvement was seen after 5 months (20 week). On follow up 23.91 % children had relapsed but the frequency of wet nights among these also was significantly low (mean wet nights 0.08/week). Even among failures there was a significant decrease in mean number of wet nights (from 4.24 wet nights/week to 1.85 wet nights/week). Conclusions: Alarm treatment was an effective intervention for management of primary monosymptomatic nocturnal enuresis with high success and low relapse rate.